The Role of Sharia Banks in Sustainable Development During Indonesia's Economic Recovery Post-Covid-19 - Dharmayanti, Diah; Abdul Aziz; Suhariyanto, Joko; Setyadi, Yusuf (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Since Covid-19 appeared three years ago an undeniable economic recession has hit the world including Indonesia, the economy has slid drastically to minus 5 in 2020-2021. However, it finally revived after the new normal adaptation era in 2022, GDP showed a positive trend. This is of course because the role of Sharia banking, especially in assisting the national economic recovery program, shows a significant level. Research using a qualitative approach through descriptive methods yields findings that Indonesia's GDP per capita increases from 57.3 in 2022 to IDR 62.1 million in 2021 (an increase of 8.6%) equivalent to USD 4,349.5. The PEN program in 2021 also experienced a ceiling increase of Rp. 658.6 T (88.4%) from a ceiling of Rp. 744.77 T which was higher than the previous year of Rp. 575.8 T. The role and contribution of Sharia banks in serving financing in the MSME sector is becoming thing done completely. This is the achievement of Islamic banking in the new normal adaptation time of the Covid-19 outbreak.